Analysis of The Impact of Taylor's Monetary Policy Provisions on Indonesian Economic Growth - Dewi, Anita Kusuma (Kirana Publisher (KNPub), 2023)
Taylor's provisions use investment credit interest rates, inflation gaps and output gaps as variables. This study seeks to analyze how the Taylor Rules variable is applied when used in Indonesia, as well as to determine the impact on economic growth in Indonesia. The purpose of this study was to determine the effect of Taylor's monetary policy variables on Indonesia's economic growth. This research method uses primary data and uses the Vector Error Correction Model (VECM) method. The results of the study show that investment credit interest rates, inflation GAP, GDP GAP, inflation and GDP have an effect on economic growth.